Synthesis of Polythiophene-Polyurethane Soft Nanoparticles for Bioimaging Applications - Karabacak, Soner; Karabacak, Soner; Yıldız, Ümit Hakan (Izmir Institute of Technology, 2020)
In this study, synthesis of fluorescent polythiophene and polyurethane soft nanoparticles carrying them was carried out for bioimaging applications. Conjugated polythiophenes and polyurethane derivatives were obtained by changing their structural properties such as size, charge, and group, and were characterized by nuclear magnetic resonance, infrared spectroscopy, dynamic functional light scattering, fluorescent microscopy, methods. In the study, changing characteristics of polyurethane nanoparticle materials were investigated depending on the synthesis conditions. Synthesis of polyurethane nanoparticles was carried out by miniemulsion polymerization technique and synthesized as nanosphere to be more controllable on nanoparticle size, morphology and stability. The sizes of the polyurethane nanospheres varied in the range from 10 to 500 nm. Polyelectrolyte-polyelectrolyte complexation was investigated using cationic polythiophene-anionic polythiophene for use in bioimaging applications. Synthesized conjugated polythiophenes are divided into two groups as anionic and cationic polythiophenes. In this thesis, three kinds of cationic polythiophene synthesis are included, but poly (1,4-dimethyl-1- (3- ((4-methylthiophene-3-yl) oxy) propyl) piperazine-1-ium bromide) (PT4) was used as cationic conjugated polythiophene in the studies. Anionic polythiophene acetic acid (PTAA) was used as a counter-charged polythiophene. In addition to these studies, dual-mode imaging agents were prepared, consisting of PTAA as fluorescent agent and gadolinium metals as magnetic agent. The bioimaging studies continued under conditions imitating biological systems, and the potential of the proposed bioimaging agents was investigated.

Bu çalışmada biyogörüntüleme uygulamaları için floresan politiyofen ve onları taşıyan poliüretan yumuşak nanoparçacıkların sentezi gerçekleştirilmiştir. Konjuge politiyofenler ve poliüretan türevleri, boyut, yük, fonksiyonel grup gibi yapısal özellikleri değiştirilerek elde edilmiş ve nükleer manyetik rezonans, kızıl ötesi spektroskopi, dinamik ışık saçılması, floresan mikroskop, metotları ile karakterize edilmiştir. Çalışmada, sentez koşullarına bağlı olarak poliüretan nanoparçacık malzemelerin değişen karakteristik özellikleri araştırılmıştır. Poliüretan nanoparçacıkların sentezi, nanoparçacık boyutu, morfolojisi ve stabilitesi üzerinde daha kontrol edilebilir olması için miniemülsiyon polimerizasyon tekniği ile gerçekleştirilmiş ve nanoküre olarak sentezlenmiştir. Elde edilen poliüretan nanokürelerin boyutları 10-500 nm aralığında değişmektedir. Biyogörüntüleme uygulamalarında kullanmak için katyonik politiyofen-anyonik politiyofen polielektrolit-polielektrolit kompleksleşmesi incelenmiştir. Sentezlenmiş konjuge politiyofenler, anyonik ve katyonik politiyofenler olarak iki gruptadır. Bu tezde üç çeşit katyonik politiyofen sentezine yer verilmiştir ancak poli (1,4-dimetil-1- (3- ((4-metiltiofen-3-il) oksi) propil) piperazin-1-ium bromür) (PT4) çalışmalarda katyonik konjuge politiyofen olarak kullanılmıştır. Anyonik politiyofen asetik asit (PTAA) karşıt yüklü politiyofen olarak kullanılmıştır. Bu çalışmalara ek olarak, floresan ajan olarak PTAA ve manyetik ajan olarak gadolinyum metallerden oluşan çift modlu görüntüleme ajanları hazırlanmıştır. Biyolojik sistemleri taklit eden koşullar altında biyogörüntüleme çalışmaları devam edilerek önerilen biyogörüntüleme ajanlarının potansiyeli araştırılmış ve uygulama alanlarına yönelik ön çalışmalar gerçekleştirilmiştir.
Biyogörüntülüme Uygulamaları için Politiyofen-poliüretan Yumuşak Nanoparçacıkların Sentezi
Thesis (Master)--Izmir Institute of Technology, Chemistry, Izmir, 2020
Includes bibliographical references (leaves: 82-86)
Text in English; Abstract: Turkish and English
Keywords: Bioimaging applications; Polyurethane nanosphere; Miniemulsion polymerization; Imaging systems in chemistry